2019
DOI: 10.2196/10432
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Emotional and Pain-Related Language in Tweets About Dentists and Medical Doctors: Text Analysis of Twitter Content

Abstract: Background Social media provides people with easy ways to communicate their attitudes and feelings to a wide audience. Many people, unfortunately, have negative associations and feelings about dental treatment due to former painful experiences. Previous research indicates that there might be a pervasive and negative occupational stereotype related to dentists and that this stereotype is expressed in many different venues, including movies and literature. Objective This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The number of sites which contain client testimonials has increased by three times (in absolute terms). The presence of comments on social networks generated by various users provides useful feedback to other potential clients through experience sharing [74]. As a consequence of widespread use of smartphones in 2021, 92% of websites make use of Google Maps in order to help to locate the businesses' addresses (of course, these are also in clear-text).…”
Section: Websites and Facebook Profilesmentioning
confidence: 99%
“…The number of sites which contain client testimonials has increased by three times (in absolute terms). The presence of comments on social networks generated by various users provides useful feedback to other potential clients through experience sharing [74]. As a consequence of widespread use of smartphones in 2021, 92% of websites make use of Google Maps in order to help to locate the businesses' addresses (of course, these are also in clear-text).…”
Section: Websites and Facebook Profilesmentioning
confidence: 99%
“…In the 21st century, social media such as Whatsapp, Facebook, Twitter and Instagram became the central platform for communication, information and advertising (Johnsen, Eggesvik, Rorvik, Hanssen, Wynn & Kummervold, 2019; Parmar, Dong & Eisingerich, 2018). The ability to provide information on social media quickly enabled patients to be informed in the field of health (El Tantawi, Al‐Ansari, AlSubaie, Fathy, Aly & Mohamed, 2018; Gao, Al‐Ansari, AlSubaie, Fathy, Aly & Mohamed, 2013; Parmar et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Parmar et al ., 2018). The use of social media is also increasing in dentistry, and it is also possible to communicate with dentists and patients (Gholami‐Kordkheili, Wild & Strech, 2013; Johnsen et al ., 2019; Melkers, Hicks, Rosenblum, Isett & Elliott, 2017; Parmar et al ., 2018). In addition, ever since the novel coronavirus disease (COVID‐19) outbreak in China has spread globally, it has a real challenge for dentists, as the virus can spread from person to person via respiratory droplets (Ahmed, Jouhar, Ahmed et al ., 2020; Sarfaraz, Jouhar, Ahmed et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fear and anxiety about visiting the dentist is an important problem for many people. In their study on Twitter, Johnsen et al [ 12 ] reported that more negative words were used in the tweets about dentists than medical doctors and that the words related to pain were used at higher rates. Pain is an unpleasant sensory and emotional experience, and it has different personal effects on different people [ 13 14 ].…”
Section: Discussionmentioning
confidence: 99%